FORMACIÓN DE LA HABILIDAD ORGANIZATIVA EN LA PROFESIÓN PEDAGÓGICA: THE FORMATION OF THE ORGANIZING SKILL IN THE PEDAGOGICAL PROFESSION - Mulet González, Manuel A.; Álvarez Suárez, Omar; Izquierdo Arias, Raida (Opuntia Brava, 2018)
En el artículo se fundamenta la importancia de la habilidad organizativa en la profesión pedagógica para la realización exitosa de la labor educativa en la clase, específicamente, para lograr el vínculo con la futura profesión. Se argumenta la necesidad de la formación profesional del maestro desde las habilidades. ABSTRACT This article supports the importance of the organizing skill in the pedagogical profession for the successful realization of the educative labor in classes, specifically for getting the bind with the future profession. It is supported the need of professional formation of teachers from the skill point of view. KEY WORDS: Organizational skill, pedagogical professional skill, educative labor